PENGARUH KEPEMIMPINAN DAN REWARDS DENGAN MEDIATOR MOTIVASI KERJA TERHADAP KINERJA TEKNISI POLITEKNIK NEGERI SEMARANG - Nugroho, Fajar Jati (Bangun Rekaprima, 2024)
Rewards and awards are an effective way to motivate employees and improve their performance. In addition to the role of compensation, leadership also plays an important role in technician performance. Effective leadership can provide clear direction, strong support, and the motivation needed to help technicians achieve optimal performance levels. The purpose of this study was to clarify the role of work motivation as a mediator of leadership and rewards on engineer performance. This study was conducted at Semarang State University of Technology using an online questionnaire. The sample of this study was engineers working at Semarang State University of Technology. The data obtained were processed using Partial Least Square (PLS). The results of the study are as follows: (1) Compensation does not affect engineer performance, (2) Leadership does not affect engineer performance, and (3) Compensation does not affect work motivation does not affect work motivation; (5) Work motivation has a positive and significant effect on employee performance; (6) Motivation has a positive and significant effect on employee performance. (7) Motivation can mediate the relationship between compensation and engineer performance.